2001
DOI: 10.1016/s0040-1625(99)00095-5
|View full text |Cite
|
Sign up to set email alerts
|

Potential Diffusion of Expert Systems in Forecasting

Abstract: We drew upon findings from the diffusion literature to assess the prospects for the diffusion of expert systems in forecasting. Forecasters judged potential adoption of expert systems in relation to two techniques that had been widely adopted in the past, Box-Jenkins and scenarios. They also rated each technique on seven innovation characteristics: relative advantage, compatibility, divisibility, communicability, complexity, product risks, and psychological risks. The respondents were classified by four foreca… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2001
2001
2015
2015

Publication Types

Select...
3
2

Relationship

0
5

Authors

Journals

citations
Cited by 9 publications
(2 citation statements)
references
References 12 publications
0
2
0
Order By: Relevance
“…After all, how many of us would be agreeable to our organizations replacing us with an expert system? Armstrong and Yokum (2000) found that potential adopters perceived significant risks associated with the use of expert systems. On the other hand, they viewed expert systems positively with respect to their compatibility with their job, the ability to experiment with parts of the system, and ease of understanding.…”
Section: Risksmentioning
confidence: 99%
“…After all, how many of us would be agreeable to our organizations replacing us with an expert system? Armstrong and Yokum (2000) found that potential adopters perceived significant risks associated with the use of expert systems. On the other hand, they viewed expert systems positively with respect to their compatibility with their job, the ability to experiment with parts of the system, and ease of understanding.…”
Section: Risksmentioning
confidence: 99%
“…Institutes have already begun conforming to change by incorporating novel methods of teaching to courses syllabi and making use of computers, when possible. In particular, expert systems have reasonable prospects for diffusion and proliferation (Armstrong and Yokum, 2001). However, they are not yet actively represented in traditional lectures of Business Forecasting and Management courses.…”
Section: Introductionmentioning
confidence: 99%